2019
DOI: 10.26434/chemrxiv.10728128.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Is Preservation of Symmetry Necessary for Coarse-Graining?

Abstract: This work investigates how preservation of molecular symmetry affects accuracy of coarse-grained (CG) molecular dynamics simulation. We studied 26 mapping operators for 7 molecules to find that it has little effect on accuracy of CG simulations.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Chakraborty et al recently showed that CG-mapping symmetry has a negligible impact on structural accuracy. 38 Asymmetry indeed appears to be irrelevant for SP models. However, the use of asymmetric CG mappings will hurt the transferability in the EE scheme.…”
Section: State-point Specific Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chakraborty et al recently showed that CG-mapping symmetry has a negligible impact on structural accuracy. 38 Asymmetry indeed appears to be irrelevant for SP models. However, the use of asymmetric CG mappings will hurt the transferability in the EE scheme.…”
Section: State-point Specific Modelsmentioning
confidence: 99%
“…Low performance stems from certain functional groups that promote vastly different conformational ensembles depending on the environment and molecular topology. An extended-ensemble average over the structural correlations of these functional groups does not capture the specificity of these diverging conformational states, and instead suggests the need for an improved mapping [38][39][40] or an increased force-field complexity. 33,[41][42][43] We validate the transferability of the derived potentials by running CG simulations on compounds that were not used in the extendedensemble training set and find that the accuracy of the CG RDFs is on par with that of the representative compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Systematic parametrization schemes exist, such as iterative Boltzmann inversion or force matching, accompanied by convenient software platforms [95,96]. Aside from the CG potentials, bottom-up strategies can strongly benefit from a more systematic optimization of the mapping itself [97,98]. Combinations of structure-based CG and ML have recently sparked interest and are quickly enabling new avenues, see below Section 2.5.3.…”
Section: Force-field Parametrizationmentioning
confidence: 99%
“…The experiment will run 5 iterations. At i-th iteration (i ∈ [1,5]), the i-th split of the dataset is regarded as testing set (groundtruth partition B is not used) and rest 4 splits of the dataset is regarded as the training set (ground-truth partition B is used for training). Therefore, after training, DSGPM is evaluated on unseen molecules in the testing set.…”
Section: Evaluation Metricsmentioning
confidence: 99%